Ecological Drivers of Molt‐Breeding Overlap, an Unusual Life‐History Strategy of Small‐Island Birds? - Christopher C. De Ruyck; Nicola Koper (Ecology and Evolution)
ABSTRACT Terrestrial bird populations on small, species depauperate islands often experience selection for generalist foraging traits via ecological release; however, it is unclear how island conditions may uniquely influence other life‐history characteristics of small‐island birds, such as the unusually high rates of molt‐breeding overlap exhibited on the island of Grenada. To explore this question, we collected data on the life cycles and diets of 10 commonly occurring Grenadian bird species to assess the degree of generalist foraging and evaluate how seasonal patterns in diet niche breadth and diet overlap among species relates to the high rates of molt‐breeding overlap. We evaluated three hypotheses explaining drivers of molt‐breeding overlap (constraints on molt rate, unpredictable food abundance, and limited duration of food abundance), and suggest that widespread overlap in small‐island tropical communities may be the result of generalist foraging adaptations and restricted time periods of sufficient invertebrate availability for successful breeding and molt to occur. We found that these species typically exhibited low breeding period seasonality followed by synchronized peaks in molt intensity and molt‐breeding overlap during peak rainfall and high invertebrate abundance. There was also greater diet overlap and wider niche widths of invertebrate resources in the wet season when molt‐breeding overlap occurred, and greater niche partitioning of invertebrate items among species in the dry season suggesting that competitive interactions for invertebrates were stronger in the dry season. Birds also shared more plant food sources in the dry season when invertebrate abundance is low, though seasonal differences in plant diet diversity and niche width varied by species. These results provide evidence that scarce invertebrate resources and competition likely limit productivity and molt/self‐maintenance in these island‐adapted, species‐depauperate communities, and drive high rates of molt‐breeding overlap, a relatively uncommon life‐history strategy.